Impact of device landing zone calcification patterns on paravalvular regurgitation after transcatheter aortic valve replacement with different next-generation devices. Issue 1 (10th May 2020) - Mauri, Victor; Frohn, Thomas; Deuschl, Florian; Mohemed, Kawa; Kuhr, Kathrin; Reimann, Andreas; Körber, Maria Isabel; Schofer, Niklas; Adam, Matti; Friedrichs, Kai; Kuhn, Elmar W; Scholtz, Smita; et al.
Abstract : Objective: Residual paravalvular regurgitation (PVR) has been associated to adverse outcomes after transcatheter aortic valve replacement (TAVR). This study sought to evaluate the impact of device landing zone (DLZ) calcification on residual PVR after TAVR with different next-generation transcatheter heart valves. Methods: 642 patients underwent TAVR with a SAPIEN 3 (S3; n=292), ACURATE neo (NEO; n=166), Evolut R (ER; n=132) or Lotus (n=52). Extent, location and asymmetry of DLZ calcification were assessed from contrast-enhanced CT imaging and correlated to PVR at discharge. Results: PVR was ≥moderate in 0.7% of S3 patients, 9.6% of NEO patients, 9.8% of ER patients and 0% of Lotus patients (p<0.001), and these differences remained after matching for total DLZ calcium volume. The amount of DLZ calcium was significantly related to the degree of PVR in patients treated with S3 (p=0.045), NEO (p=0.004) and ER (p<0.001), but not in Lotus patients (p=0.698). The incidence of PVR ≥moderate increased significantly over the tertiles of DLZ calcium volume (p=0.046). On multivariable analysis, calcification of the aortic valve cusps, LVOT calcification and the use of self-expanding transcatheter aortic valve implantation (TAVI) prostheses emerged as predictors of PVR. Conclusions: The susceptibility to PVR depending on the amount of calcium was mainly observed in self-expanding TAVI prostheses. Thus, DLZ calcification is an important factor to be considered in prosthesis selection for each individual patient, keeping in mind the trade-off between PVR reduction, risk of new pacemaker implantation and unfavourable valve ha emodynamics.